Determining the Drivers of Mosquito and Fish Distributions In An Urban, Riverine Rock Pool Metacommunity - Kernstine, Melissa A (East Carolina University, 2021)
Metacommunities and metapopulations are comprised of interconnected patches of habitat linked by dispersal, which has traditionally been considered a stochastic process in which organisms move across space randomly. Recently it has been shown that some organisms exhibit patterns of preference and avoidance of certain habitat patches based on habitat quality. Thus habitat qualities such as predator presence or habitat patch size influence the spatial distributions and abundances of organisms in a metacommunity. In these collective studies we conducted analyses of a variety of abiotic and biotic environmental characteristics of riverine rock pool metacommunities that we considered important in explaining mosquito and fish distributions. We specifically analyzed a long- term dataset and an extensive system-wide snapshot dataset to first determine whether these two organisms exhibited expectations of complete spatial randomness (CSR). We then analyzed what ecological factors were important for their presence and abundance and generated georeferenced spatially-predictive maps from their modelled distributions. Our results showed that mosquito and fish distributions were associated with a combination of abiotic (such as bottom substrate type and water clarity) and biotic (such as predator presence) factors and that they deviated from CSR in regards to individual rock pool locations as well as each other. After establishing that these organisms were not randomly distributed amongst the rock pool metacommunity, we analyzed the snapshot dataset to determine whether the distance to the nearest fish influenced the probability of mosquito occupancy in a pool. Fish have been known to induce an oviposition behavior modification in mosquitoes, in addition to eating their prey, called spatial contagion. This occurs when mosquitoes may either avoid habitat patches near those with predators despite good habitat qualities, or choose predator-rich patches located near predator-free patches due to positive cue emission from predator-free habitat. Our results indicated that increasing distances to a fish pool subsequently increased the probability of mosquito occupancy, alongside many other environmental factors. We then conducted a Before-After-Control-Impact study using Gambusia holbrooki (a predatory species of mosquitoes) to experimentally test this hypothesis in our system. Although we had provided some evidence for spatial contagion from these analyses, we could not conclusively determine whether it is important in explaining mosquito distributions and abundances when co-occurring with other local and regional processes in such a noisy and variable system. Disentangling these processes influencing species' distributions will further our understanding of how organisms interact within metacommunities as well as facilitate our ability to predict where they may be located in space.
Keywords: spatial distributions; ecological niche modeling; mosquito distributions; fish distributions; spatial contagion; metacommunity; metapopulation; occupancy; abundance; Spatial ecology; Predation (Biology); Mosquitoes--Population; Fishes--Population